Histopathological spectrum of renal lesions in autopsy cases: Correlation with kidney weight and cause of death (Journal of Forensic Medicine & Toxicology, 2026)
Autopsy-based histopathological evaluation of kidneys provides essential insight into the prevalence and spectrum of  renal disease, especially in cases where renal dysfunction remains undiagnosed during life. The present study aimed to  analyze the morphological and microscopic renal lesions in medicolegal autopsies, correlating them with demographic  variables, kidney weight, and cause of death. A total of 100 autopsy cases were studied in the Department of Forensic  Medicine, Government Medical College, Amritsar. Gross kidney features including size, surface, and weight were  recorded, and histopathological examination was performed using hematoxylin and eosin staining. Out of 100 cases, 75  showed renal lesions while 25 had normal histology and non-glomerular lesions were more common than glomerular  ones. The most frequent findings were acute tubular necrosis, arteriosclerosis, and chronic pyelonephritis. Renal pathol ogies were most frequently detected in poisoning and cardiovascular deaths. These findings highlight the importance of  routine renal histopathological examination in all autopsies for improved understanding of hidden renal morbidity and  systemic pathology, analyzing their association with demographic variables, kidney weight, and cause of death.
Keywords: Autopsy; Histopathology; Cause of Death; Acute Tubular Necrosis: Arteriosclerosis